The role of innovation capability and social media marketing capability to improve SME’s social media performance - Sabandar, Michelle Clysia; Jimmy, Yohanes; Imran, Muhammad (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2023)
This study aims to determine the influence of Social Media Marketing Communication Capability, Social Media Product Development, and Innovation Capability on whether to produce Social Media Performance for SMEs Florist in Java. This quantitative study uses a purposive sampling technique that analyzes 98 respondents collected using an online questionnaire. The theory used is Resource Based Theory (RBT), where analysis techniques using SMART-PLS. The results showed that Innovation Capability did not produce Social Media Performance with a t-value of 0.618 and a p-value of 0.537. Social Media Marketing Communication Capability can also not create Social Media Performance with a t-value of 1.085 and a p-value of 0.278. Meanwhile, Social Media Product Development Capability has a significant role in creating Social Media Performance. This study concludes from these three variables, only Social Media Product Development has an essential role in producing Social Media Performance.